2021
DOI: 10.1186/s13073-021-00910-1
|View full text |Cite
|
Sign up to set email alerts
|

Landscape and selection of vaccine epitopes in SARS-CoV-2

Abstract: Background Early in the pandemic, we designed a SARS-CoV-2 peptide vaccine containing epitope regions optimized for concurrent B cell, CD4+ T cell, and CD8+ T cell stimulation. The rationale for this design was to drive both humoral and cellular immunity with high specificity while avoiding undesired effects such as antibody-dependent enhancement (ADE). Methods We explored the set of computationally predicted SARS-CoV-2 HLA-I and HLA-II ligands, ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 179 publications
(112 reference statements)
2
27
0
Order By: Relevance
“…Pioneering bioinformatic studies focused on predicting cytotoxic epitopes of a limited subset of common HLA alleles against the reference viral strain [ 12 , 19 , 22 , 25 ]. Former high-range reports have explored the epitope space of the virus with different purposes such as the assessment of the geographical prevalence of allele-peptide combinations [ 26 ] and the design of epitope-based vaccines [ 27 ]. However, SARS-CoV-2 has substantially evolved after more than a year of pandemic, resulting in a human-viral combination landscape of immense scale only approachable using automated techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering bioinformatic studies focused on predicting cytotoxic epitopes of a limited subset of common HLA alleles against the reference viral strain [ 12 , 19 , 22 , 25 ]. Former high-range reports have explored the epitope space of the virus with different purposes such as the assessment of the geographical prevalence of allele-peptide combinations [ 26 ] and the design of epitope-based vaccines [ 27 ]. However, SARS-CoV-2 has substantially evolved after more than a year of pandemic, resulting in a human-viral combination landscape of immense scale only approachable using automated techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Most indels are significantly (q-value < 0.01 and odds ratio >1) concentrated in NSP1, NSP3, NSP6, ORF3a, ORF6, ORF7a, ORF7b, ORF8, nucleocapsid, and spike glycoprotein ( Figure 1E and Table 1 ), all of which are involved in interactions with the host immune system ( Lei et al, 2020 ; Liang et al, 2021 ; Smith et al, 2021 ). At the same time, proteins involved in the replication–transcription complex show very few or no indels ( Figure 1E and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Aggregation and recurrence of indels in hypervariable regions of SARS-CoV-2 proteins are determined by an interplay of the protein structural constraints and functional role of specific regions. Most of the HVRs of SARS-CoV-2 proteins (except ORF7a-HVR) are found on or adjacent to loops forming either experimentally identified ( Liang et al, 2021 ; Smith et al, 2021 ) or predicted antibody epitopes ( Figures 2 , 3 ), suggesting SARS-CoV-2 is optimizing its interactions with the host immune system, possibly in response to the increased immunity of the population. For instance, NSP6-HVR falls on a predicted T-cells ( Smith et al, 2021 ) and B-cells epitope (per IEDB server), forming a short loop between two transmembrane helices ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…One such example was highlighted by a recent study where PhIP-Seq revealed that vaccination (as compared to SARS-CoV-2 infections) generated more diverse antibody epitopes [ 41 ]. Another study utilized PhIP-Seq epitope mapping data from COVID-19 patients to identify dominant linear B cell epitope regions and then rationally design peptide vaccine candidates against SARS-CoV-2 [ 42 ].…”
Section: Applications Of Phip-seq In Sero-epidemiologymentioning
confidence: 99%